The synthesis and structure–property relation analysis of metal chalcohalide crystals Cs2InPS4X2 (X = Cl, Br) with mixed anions. Issue 12 (4th March 2022) - Tang, Chunlan; Xing, Wenhao; Wang, Naizheng; Tang, Jian; Lin, Zheshuai; Wu, Jieyun; Yin, Wenlong; Kang, Bin
Abstract : Two novel metal chalcogenides Cs2 InPS4 X2 (X = Cl, Br) were successfully synthesized and exhibit large optical band gaps induced by the [InS4 X2 ] 7− mixed-anion groups. Abstract : Inorganic metal chalcohalides are significant semiconductive materials for photovoltaics, photodetetion and infrared optics. Thus it is considerably rewarding to develop a new synthetic strategy to provide more degrees of freedom for atomic coordination to tune the optical and electronic properties of metal chalcohalides. In this work, the mixed-anion strategy is performed to synthesize two new metal chalcohalides Cs2 InPS4 X2 (X = Cl, Br) with mixed-anion structure by the reaction of InPS4 and CsX. Single-crystal X-ray diffraction analysis shows that they are isostructural and crystallize in the centrosymmetric space group P 21 / n, consisting of zero-dimensional structure [In2 P2 S8 X4 ] 4− (X = Cl, Br) built from tetrahedral [PS4 ] 3− and octahedral [InS4 X2 ] 7− (X = Cl, Br) through edge-sharing, with Cs cations filling in intervening voids. The UV-vis-NIR diffuse reflectance spectroscopy measurement reveals that Cs2 InPS4 Cl2 and Cs2 InPS4 Br2 exhibit large optical bandgaps of 3.21 eV and 3.12 eV, respectively. The electronic structure calculations show that the bandgap mainly originates from the [InS4 X2 ] 7− (X = Cl, Br) mixed-anion groups. First-principles calculations indicate that the birefringence of Cs2 InPS4 Cl2 and Cs2 InPS4 Br2 is ∼0.08 and ∼0.05 at 2090 nm, respectively. Furthermore, thermal analysis reveals that the Cs2 InPS4 X2 (X = Cl, Br) are thermostable up to 400 °C. This discovery enriches the structural diversity of inorganic chalcohalides and provides an insight for the exploration of new semiconductive materials.